2023
DOI: 10.1002/advs.202303575
|View full text |Cite
|
Sign up to set email alerts
|

Motile Living Biobots Self‐Construct from Adult Human Somatic Progenitor Seed Cells

Gizem Gumuskaya,
Pranjal Srivastava,
Ben G. Cooper
et al.

Abstract: Fundamental knowledge gaps exist about the plasticity of cells from adult soma and the potential diversity of body shape and behavior in living constructs derived from genetically wild‐type cells. Here anthrobots are introduced, a spheroid‐shaped multicellular biological robot (biobot) platform with diameters ranging from 30 to 500 microns and cilia‐powered locomotive abilities. Each Anthrobot begins as a single cell, derived from the adult human lung, and self‐constructs into a multicellular motile biobot aft… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…Existing real-world biological examples of releasing sub-agents from explicit control, to ask what they would do if allowed, include the engineering of biobots. It has recently been shown that un-modified, genetically-normal cells self-assemble into constructs with novel behaviors when freed from the instructive influence of their neighbors (Blackiston et al, 2023;Gumuskaya et al, 2023), revealing baseline competencies not apparent from their standard role within default developmental algorithms. The minimal model shown here represents a first step toward the development of more general strategies to study emergent goals in collective systems and ways in which those goals cooperate with, compete with, and alter the performance of explicit goals we (or evolution) instantiate via hardware or software mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing real-world biological examples of releasing sub-agents from explicit control, to ask what they would do if allowed, include the engineering of biobots. It has recently been shown that un-modified, genetically-normal cells self-assemble into constructs with novel behaviors when freed from the instructive influence of their neighbors (Blackiston et al, 2023;Gumuskaya et al, 2023), revealing baseline competencies not apparent from their standard role within default developmental algorithms. The minimal model shown here represents a first step toward the development of more general strategies to study emergent goals in collective systems and ways in which those goals cooperate with, compete with, and alter the performance of explicit goals we (or evolution) instantiate via hardware or software mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Here, in keeping with an emphasis on basal (minimal) cognition, "goal" is used not to refer to a high-order, metacognitive "known purpose" as seen in human behavior, but rather in its minimal cybernetic (Rosenblueth et al, 1943) definition of a target state that a system has some ability to reach, despite a range of challenges. Learning to predict and control the goals of collective systems-especially newly engineered systems-is likely to be of existential importance to human flourishing over the coming decades in areas ranging from swarm robotics to AI systems to bioengineered tissues (Ebrahimkhani & Levin, 2021;Gumuskaya et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…It cannot take for granted how much genetic material it will have [117], how many cells [120][121][122], or what size cells [116], it will have (in addition to any external damage it might sustain, or the chemical details of its environment -even the internal parts cannot be assumed to be the same as those with which its past genome was forged) 38 . Beyond the incredible robustness of standard form and function, we see adaptation to extreme changes of conditions, with no need for transgenes or genomic editing, in the spontaneous emergence of Xenobots [123][124][125], Anthrobots [126], and plant galls [127] (constructions of leaf cells hacked by signals from a non-human bioengineer to produce a totally new and complex pattern, Figure 5). This is also probably why chimerism and bioengineering, at all scales, workscoherent outcomes often result from combining not only divergent living components from different lineages [128] but also totally un-natural and novel engineered components, from nanomaterials to smart implants [129][130][131][132][133][134] (Figure 6).…”
Section: (A) (B)mentioning
confidence: 99%
“…It cannot take for granted how much genetic material it will have [143], or how many cells [146][147][148], or what size cells [142], it will have (in addition to any external damage it might sustain, or the chemical details of its environment-even the internal parts cannot be assumed to be the same as those with which its past genome was forged). Beyond the incredible robustness of standard form and function, we see adaptation to extreme changes of conditions, with no need for transgenes or genomic editing, in the spontaneous emergence of Xenobots [149][150][151], Anthrobots [152], and plant galls [153] (constructions of leaf cells hacked by signals from a non-human bioengineer to produce a totally new and complex pattern, as shown in Figure 5). This is also probably why chimerism and bioengineering, at all scales, work-coherent outcomes often result from combining not only divergent living components from different lineages [154] but also totally unnatural and novel engineered components, from nanomaterials to smart implants [155][156][157][158][159][160] (Figure 6).…”
Section: Beyond the Brain: Bowties Everywherementioning
confidence: 99%